Dynamic Prognostication in Critically Ill Cirrhotic Patients With Multiorgan Failure in ICUs in Europe and North America: A Multicenter Analysis*. Issue 11 (November 2018) - Karvellas, Constantine J.; Garcia-Lopez, Elisabet; Fernandez, Javier; Saliba, Faouzi; Sy, Eric; Jalan, Rajiv; Pavesi, Marco; Gustot, Thierry; Ronco, Juan J.; Arroyo, Vicente
Abstract : Objectives: To evaluate the Chronic Liver Failure-Consortium Acute on Chronic Liver Failure score in acute on chronic liver failure patients admitted to ICUs from different global regions and compare discrimination ability with previously published scores. Design: Retrospective pooled analysis. Setting: Academic ICUs in Canada (Edmonton, Vancouver) and Europe (Paris, Barcelona, Chronic liver failure/Acute-on-Chronic Liver Failure in Cirrhosis [CANONIC] study). Patients: Sample of analysis of 867 cirrhotic patients with acute on chronic liver failure admitted to ICU. Cumulative incidence functions of death were estimated by acute on chronic liver failure grade at admission and at day 3. Survival discrimination abilities of Chronic Liver Failure-Consortium Acute on Chronic Liver Failure, Model for End-Stage Liver Disease, Acute Physiology and Chronic Health Evaluation II, and Child-Turcotte-Pugh scores were compared. Interventions: ICU admission for organ support. Measurements and Main Results: At admission 169 subjects (19%) had acute on chronic liver failure 1, 302 (35%) acute on chronic liver failure 2, and 396 (46%) had acute on chronic liver failure 3 with 90-mortality rates of 33%, 40%, and 74%, respectively ( p < 0.001). At admission, Chronic Liver Failure-Consortium Acute on Chronic Liver Failure demonstrated superior discrimination at 90 days compared with Acute Physiology and Chronic Health Evaluation II ( n = 532; concordance index 0.67 vs 0.62; p = 0.0027) and Child-Turcotte-Pugh ( n = 666; 0.68 vs 0.64; p = 0.0035), but not Model for End-Stage Liver Disease ( n = 845; 0.68 vs 0.67; p = 0.3). A Chronic Liver Failure-Consortium Acute on Chronic Liver Failure score greater than 70 at admission or on day 3 was associated with 90-day mortality rates of approximately 90%. Ninety-day mortality in grade 3 acute on chronic liver failure patients at admission who demonstrated improvement by day 3 was 40% (vs 79% in patients who did not). Conclusions: The Chronic Liver Failure-Consortium Acute on Chronic Liver Failure demonstrated better discrimination at day 28 and day 90 compared with Acute Physiology and Chronic Health Evaluation II and Child-Turcotte-Pugh. Patients who demonstrated clinical improvement post-ICU admission (e.g., acute on chronic liver failure 3 to 1 or 2) at day 3 had better outcomes than those who did not. In high-risk ICU patients (Chronic Liver Failure-Consortium Acute on Chronic Liver Failure > 70), decisions regarding transition to palliation should be explored between patient families and the ICU providers after a short trial of therapy. Abstract : Supplemental Digital Content is available in the text.